Byssus as a Means of Metal Excretion Route and High Metal Levels in Fecal Materials as Metal Retention: An Experimental Laboratory Study Using Perna viridis - C. K. Yap (International Journal of Advances in Applied Sciences, 2012)
The present study aimed at determining the concentrations of Cd, Pb and Zn in fecal materials, byssus and different soft tissues of Perna viridis under controlled laboratory conditions during accumulation and depuration tests and to discuss the roles played by byssus and fecal materials in the coastal waters. The present findings indicated that the byssus of P. viridis acted as an excretion routes for Cd, Pb and Zn while mussels have a retention mechanism of metals as evidenced in the high metal levels found in the fecal materials during the experimental study. This implied that mussel population played an important role in expediting the metal cycling as well as supposedly nutrient cycling in the coastal ecosystem by rapidly recycling back to the coastal environment in the underlying sediments.